Compound technique -based inline design strategy for water-hammer control in steel pressurized-piping systems. (January 2019) - Triki, Ali; Chaker, Mohamed Amir
Abstract: The inline design strategy was recognized as being an effective tool for water-hammer control in pressurized-pipe flow. Principally, this strategy is based on replacing a short-section of the existing steel-piping system by another made of polymeric material. However, this strategy leads to an excessive radial-strain amplification and a large spread-out of wave oscillation period. Alternatively, an innovative compound technique -based inline design strategy was reported in this paper to enhance the foregoing limitations. The proposed technique is based on splitting the single short-section used in the conventional technique into a couple of two sub short-sections made up of two distinct material types. The materials demonstrated in this study include high- and low-density polyethylene (HDPE ) and (LDPE ). The transient solver was based on the1-D unconventional water-hammer model embedding the Vitkovsky et al. and Kelvin-Voigt formulation, while the numerical discretization was performed using the Fixed Gird Method of Characteristics (FG-MOC ). The proposed method is validated through a comparison with experimental results. Further, detailed numerical results obtained from several scenarios are presented and discussed. Results illustrated the reliability of the proposed technique in mitigating excessive high- or low-pressures, and evidenced that the (HDPE –LDPE ) sub short-sections combination (where the former is attached to hydraulic parts and the latter to the steel pipe) is the most prominent configuration providing an acceptable trade-off between piezometric-head and circumferential-stress attenuation (from one side), and limitation of the excessive spreading of oscillation period and amplification of radial-strain (from the other side). The findings of a parametric study of the sensitivity of pressure wave damping and spreading to the employed short-section length and diameter resulted in estimation of the near-optimal design values of the short-section size. Graphical abstract: Highlights: Improvement of the conventional technique skill in term of limitation of wave oscillation period spreading. Utilization ofHDPE /LDPE polymeric materials for the sub short-section pipe-wall material. Exploration of the amortization rates of pressure-head, circumferential-stress and radial-strain versus the sub short-section size.